Courses we take shouldn't solely be blamed for employment issues - Azrymi, Amirul Nazmi (Malaysiakini.com, 2023)
To counter the stereotype that university programmes/courses are mainly responsible for employment issues e.g. unemployment. There are other factors such as fluctuating industries, different expectations, generational gap etc.